FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI MAHASISWA EKONOMI ISLAM UNTUK BEKERJA DI LEMBAGA KEUANGAN SYARIAH - bagus, johan; Khusnia Anggraini, Ika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The existence of this study aims to determine whether there is influence from knowledge of Islamic finance, spiritual motivation, and financial rewards on the preferences of Islamic economics students to work in Islamic financial institutions. This research only focuses on students of Islamic economics, Faculty of Economics and Business, Universitas Brawijaya, class of 2014-2019. This study uses a quantitative approach where data is obtained through a questionnaire using a Likert scale. There were 90 sample respondents consisting of 49 male respondents and 41 female respondents. Data testing was carried out using the help of SPSS software, the method applied was multiple linear regression analysis. The results of the study show that knowledge of Islamic finance and spiritual motivation have an influence on preferences for working in Islamic financial institutions. Meanwhile, financial income has no effect on preferences to work in Islamic financial institutions. Meanwhile, knowledge of Islamic finance, spiritual motivation, and financial rewards explains 45.1% of the preference for working in Islamic financial institutions.